2012
DOI: 10.1242/dev.077263
|View full text |Cite
|
Sign up to set email alerts
|

Celf1 regulation of dmrt2a is required for somite symmetry and left-right patterning during zebrafish development

Abstract: SUMMARYRNA-binding proteins (RBPs) bind to numerous and diverse mRNAs to control gene expression post-transcriptionally, although the in vivo functions of specific RBP-mRNA interactions remain largely unknown. Here, we show that an RBP named Cugbp, Elav-like family member 1 (Celf1) controls expression of a gene named doublesex and mab-3 related transcription factor 2a (dmrt2a), which is essential for somite symmetry and left-right patterning during zebrafish development. Celf1 promotes dmrt2a mRNA decay by bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…In addition, we recently showed that celf1 is required for somite symmetry and cardiac laterality [13]. In the course of our investigation of other laterality organs such as liver and pancreas, we find an unexpected role for celf1 in zebrafish organogenesis; celf1 is essential for the formation of endoderm-derived organs.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…In addition, we recently showed that celf1 is required for somite symmetry and cardiac laterality [13]. In the course of our investigation of other laterality organs such as liver and pancreas, we find an unexpected role for celf1 in zebrafish organogenesis; celf1 is essential for the formation of endoderm-derived organs.…”
Section: Introductionmentioning
confidence: 70%
“…Since cardiac laterality was altered in celf1 knockdown (KD) embryos [13], we reasoned that the lateralities of endoderm-derived organs such as liver, pancreas and gut are also altered in celf1 KD embryos. To test this, we injected celf1 morpholinos ( celf1 -MOs) into transgenic line Tg [ sox17:GFP ] [14], whose GFP is expressed in endoderm cells and dorsal forerunner cells, and observed the formation of endoderm-derived organs in celf1 KD embryos.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations